2013
DOI: 10.1111/aas.12109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age on minimum effective volume of local anesthetic for ultrasound‐guided supraclavicular brachial plexus block

Abstract: Within the present study, we report a reduced minimum effective anesthetic volume for ultrasound-guided supraclavicular block in elderly patients. Additionally, smaller cross-sectional surface area of brachial plexus in the supraclavicular region was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The weak positive correlation between age and size of nerves may explain the reduced minimum effective volume for ultrasound-guided brachial plexus block in elderly patients. 13 Our results showed that the mean size of all nerves was bigger in males than females, although this result was only significant for the musculocutaneous, radial and ulnar nerves. The anaesthetic implications of this finding relate to the effectiveness of brachial blocks.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The weak positive correlation between age and size of nerves may explain the reduced minimum effective volume for ultrasound-guided brachial plexus block in elderly patients. 13 Our results showed that the mean size of all nerves was bigger in males than females, although this result was only significant for the musculocutaneous, radial and ulnar nerves. The anaesthetic implications of this finding relate to the effectiveness of brachial blocks.…”
Section: Discussionmentioning
confidence: 49%
“…The weak positive correlation between age and size of nerves may explain the reduced minimum effective volume for ultrasound-guided brachial plexus block in elderly patients. 13 …”
Section: Discussionmentioning
confidence: 99%
“…In addition, most of the non-randomized trial studies have a low risk of bias in multiple domains, but there is an unclear risk in the rst domain for many of the included studies as elicited in Fig. As observed on Table 1, one of the studies was an observational study (39), three retrospective studies (24)(25)(26), four randomized control trials (27)(28)(29)(30), and 10 prospective studies (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Among the included studies, the sample sizes vary signi cantly, ranging from relatively small cohorts of 20 patients Xavier P et al, 2002 (31) to large-scale investigations such as the study by Ottokar et al, 2014 (24), which encompassed an extensive cohort of 17,157 individuals.…”
Section: Resultsmentioning
confidence: 99%
“…One prospective double-blind study reported an almost 50% decrease in minimum effective local anesthetic volume required for brachial plexus block in patients older than 65 years. [ 12 ] These patients also have smaller cross-sectional areas of the brachial plexus compared with younger patients. [ 12 ] Similar findings were shown following epidural analgesia, in which patients >70 years used lower median effective concentrations (EC50) of ropivacaine to attain complete motor blockade in the perineum or lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] These patients also have smaller cross-sectional areas of the brachial plexus compared with younger patients. [ 12 ] Similar findings were shown following epidural analgesia, in which patients >70 years used lower median effective concentrations (EC50) of ropivacaine to attain complete motor blockade in the perineum or lower limbs. [ 6 ]…”
Section: Discussionmentioning
confidence: 99%